Penerapan System Application and Product (SAP) pada Administrasi Kepegawaian Penerima SHT di PT Perkebunan Nusantara II Kebun Bandar Klippa - Munadya Puteri Andisty; Hendra Harmain (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The rapid development of information technology can now be used as a facility to facilitate all processes of managing a company's information data. With the information technology can facilitate the company in doing all its daily activities. Since January 2019 PT. Perkebunan Nusantara II has utilized this information technology, known as the SAP (System Application and Product) software, this module or application can integrate all functions of the company's sub divisions end to end, especially in the personnel administration section. The majority of phenomena directly observed at the PTPN II Kebun Bandar Klippa Office is the provision of SHT (Old Age Benefits) for employees who have entered retirement age. This research method uses descriptive qualitative analysis method, namely by using observation instruments or direct observations in the field and also documentation instruments. The research subjects in this study were 2 employees of the HR department, and the object of research in this study was the application of the SAP application itself, especially in the field of employee administration for SHT recipients. With the SAP application, it can make it easier for HR employees to input data properly and regularly and can access data quickly. Keywoard: SAP (System Application and Product), officialdom administration, SHT